Navigating the Digital Frontier: The Impact of Emerging Technologies in Libraries Services - Olafimihan, Cecilia Oyebola; Atanda, Luqman Ayanlola; Gbotosho, Ajibola Sunmade; Ekeh, Esther Motunrayo (RADINKA JAYA UTAMA PUBLISHER, 2024)
The rapid evolution of emerging technologies is revolutionizing the way libraries operate, interact with users, and provide access to information. This study explores the impact of specific emerging technologies on library services, most especially focusing on Artificial Intelligence (AI). Our research reveals that this technology have the potential to enhance user experience, improve resource discovery, and increase accessibility. However, it also pose significant challenges, such as data privacy concerns, staff training needs, and infrastructure requirements. This study provides insights into the benefits and drawbacks of emerging technologies in libraries, offering recommendations for strategic implementation and adoption.